Teachers as Connected Professionals: A Model to Support Professional Learning Through Personal Learning Networks - Oddone, Kay; Hughes, Hilary; Lupton, Mandy (International Review of Research in Open and Distributed Learning, 2019)
As education becomes increasingly complex, effective continuing professional learning is an important strategy to support teachers in schools. However, current professional development approaches may not meet contemporary teachers’ needs. Seeking to enhance teachers’ professional learning opportunities, this paper presents a model of learning as a connected professional. The model draws upon the findings of a qualitative case study of 13 teachers who interact with others through a personal learning network (PLN). Theories of connectivism, networked learning, and connected learning underpin the model, which conceptualises the whole experience of learning as a connected professional. The model comprises three elements: arenas of learning, teacher as learner, and PLN. Key characteristics of the experience are practices described as linking, stretching, and amplifying. These practices recur in various ways across all three elements of the model. The model promotes professional learning that is active, interest-driven, and autonomous, meeting personal learning needs while being socially connected. As education becomes increasingly complex, effective continuing professional learning is an important strategy to support teachers in schools. However, current professional development approaches may not meet contemporary teachers’ needs. Seeking to enhance teachers’ professional learning opportunities, this paper presents a model of learning as a connected professional. The model draws upon the findings of a qualitative case study of 13 teachers who interact with others through a personal learning network (PLN).Theories of connectivism, networked learning, and connected learning underpin the model, which conceptualises the whole experience of learning as a connected professional. The model comprises three elements: arenas of learning, teacher as learner, and PLN. Key characteristics of the experience are practices described as linking, stretching, and amplifying. These practices recur in various ways across all three elements of the model. The model promotes professional learning that is active, interest-driven, and autonomous, meeting personal learning needs while being socially connected.